6x+4(2x-11)=26

Simple and best practice solution for 6x+4(2x-11)=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4(2x-11)=26 equation:


Simplifying
6x + 4(2x + -11) = 26

Reorder the terms:
6x + 4(-11 + 2x) = 26
6x + (-11 * 4 + 2x * 4) = 26
6x + (-44 + 8x) = 26

Reorder the terms:
-44 + 6x + 8x = 26

Combine like terms: 6x + 8x = 14x
-44 + 14x = 26

Solving
-44 + 14x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '44' to each side of the equation.
-44 + 44 + 14x = 26 + 44

Combine like terms: -44 + 44 = 0
0 + 14x = 26 + 44
14x = 26 + 44

Combine like terms: 26 + 44 = 70
14x = 70

Divide each side by '14'.
x = 5

Simplifying
x = 5

See similar equations:

| 17=2(8x+5)+6(2x+9) | | -9+2wx+x=y | | -16x^2-22x+112=0 | | 2g+2(-7+5g)=1-g | | 3n+17+4n+16=180 | | 7x+4(2x-12)=27 | | n+10=-4 | | 7(8v+7)-5(6v-8)=245 | | 12=-6(n-8) | | 1/4+4x/5=12/20 | | 7(8v+7)+5(6v-8)=245 | | (X^2)-8x+137=0 | | -4y-7=3y-8 | | y+2x+60=180 | | 4/2+6t=2 | | 5/4-3/16 | | 4x-16=3x-7 | | 4y-10=3x | | 7/x+2-6=5x+14/x+2 | | -2(2+3)=2(5t-3) | | x-0.15x=55 | | 0.6666666666d+1=16-d | | 6x-4x-3=5 | | 264+26=528 | | 3x+20/4+x+38/7=14 | | x+5=5x+2 | | 2(7w+2)-4(w-7)=72 | | -4x+9=59 | | f+4overg=6 | | m/10-4=16 | | 7x+2(4x+7)=149 | | 2x+3+x=9 |

Equations solver categories